New information about the third stage larva and larval habitat of Microdon (Chymophila) bruchi Shannon, 1927 (Diptera, Syrphidae) from Argentina. Issue 45 (10th December 2019) - López-García, Guillermo P.; Reemer, Menno; Debandi, Guillermo; Mengual, Ximo
ABSTRACT: In this paper, we provide new biological information about Microdon ( Chymophila ) bruchi Shannon, 1927. We present new records of M. bruchi in nests of Camponotus mus Roger, 1863 built inside Vitis vinifera L. plants from Argentina (Mendoza Province) and records of this species for Catamarca and Entre Ríos, Argentina. DNA barcodes and data on morphology and locomotion for third-stage larvae are provided. An identification key is also given to distinguish M. bruchi from other Neotropical species of Chymophila . We designate a lectotype for Microdon bruchi Shannon, 1927, and we consider Microdon argentinae Hull, 1937 a junior synonym of M. bruchi . urn:lsid:zoobank.org:pub:D507A381-27BA-40D6-BC08-28F14579694F